Production of Salvianic Acid A from l-DOPA via Biocatalytic Cascade Reactions - Ke Shun Hu; Chong Le Chen; Huan Ru Ding; Tian Yu Wang; Qin Zhu; Yi Chen Zhou; Jia Min Chen; Jia Qi Mei; Sheng Hu; Jun Huang; Wei Rui Zhao; Le He Mei (Molecules, 2022)
Salvianic acid A (SAA), as the main bioactive component of the traditional Chinese herb Salvia miltiorrhiza, has important application value in the treatment of cardiovascular diseases. In this study, a two-step bioprocess for the preparation of SAA from l-DOPA was developed. In the first step, l-DOPA was transformed to 3,4-dihydroxyphenylalanine (DHPPA) using engineered Escherichia coli cells expressing membrane-bound L-amino acid deaminase from Proteus vulgaris. After that, the unpurified DHPPA was directly converted into SAA by permeabilized recombinant E. coli cells co-expressing d-lactate dehydrogenase from Pediococcus acidilactici and formate dehydrogenase from Mycobacterium vaccae N10. Under optimized conditions, 48.3 mM of SAA could be prepared from 50 mM of l-DOPA, with a yield of 96.6%. Therefore, the bioprocess developed here was not only environmentally friendly, but also exhibited excellent production efficiency and, thus, is promising for industrial SAA production.